2003
DOI: 10.1021/es030370y
|View full text |Cite
|
Sign up to set email alerts
|

Source Apportionment of PM2.5at an Urban IMPROVE Site in Seattle, Washington

Abstract: The multivariate receptor models Positive Matrix Factorization (PMF) and Unmix were used along with the EPA's Chemical Mass Balance model to deduce the sources of PM2.5 at a centrally located urban site in Seattle, WA. A total of 289 filter samples were obtained with an IMPROVE sampler from 1996 through 1999 and were analyzed for 31 particulate elements including temperature-resolved fractions of the particulate organic and elemental carbon. All three receptor models predicted that the major sources of PM2.5 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
142
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 238 publications
(152 citation statements)
references
References 27 publications
10
142
0
Order By: Relevance
“…Thermally derived C fractions, [53][54][55][56] which are a free byproduct of thermal/optical C analyses, have been found useful for distinguishing between diesel exhaust and other C source types. [57][58][59][60][61] For example, high-temperature EC (e.g., EC2, EC evolved at 740°C in a 98% helium [He]/2% oxygen [O 2 ] atmosphere) dominates particulate emissions from diesel engines. 54 Specific organic markers (Table 2) have also proven useful in PMF modeling studies, [63][64][65][66] but advances are needed to make them more available in source and receptor samples.…”
Section: Receptor Modeling Proceduresmentioning
confidence: 99%
“…Thermally derived C fractions, [53][54][55][56] which are a free byproduct of thermal/optical C analyses, have been found useful for distinguishing between diesel exhaust and other C source types. [57][58][59][60][61] For example, high-temperature EC (e.g., EC2, EC evolved at 740°C in a 98% helium [He]/2% oxygen [O 2 ] atmosphere) dominates particulate emissions from diesel engines. 54 Specific organic markers (Table 2) have also proven useful in PMF modeling studies, [63][64][65][66] but advances are needed to make them more available in source and receptor samples.…”
Section: Receptor Modeling Proceduresmentioning
confidence: 99%
“…[ 3 À are the dominant ions for marine cloud water collected over the eastern Pacific Ocean. [20][21][22][23][24] They also contribute 24.5 % of PM2.5 mass from continental sources. [25] Based on the Hofmeister series, ions can be divided into kosmotropes and chaotropes, which have opposing affinities towards the interface.…”
Section: Introductionmentioning
confidence: 99%
“…UNMIX has been recently utilized to establish ambient aerosol sources and was reported to provide good agreement with predictions of other multivariate receptor models (e.g. PCA/MLR, PMF), especially in identifying the dominant source categories (Henry, 2000;Lewis et al, 2003;Larsen and Baker, 2003;Maykut et al, 2003;Mukerjee et al, 2004). A summary of various recent UNMIX applications are outlined in Table 1.…”
Section: Introductionmentioning
confidence: 99%
“…The authors delineated between gasoline and diesel engine sources; the EC/OC ratio for the diesel source was 0.66, whereas it was 0.32 for the gasoline sources. Maykut et al (2003) and Kim et al (2004) reported UNMIX results for the Seattle, WA area. Maykut et al (2003) reported that carrying out the analysis with EC and OC components resulted in a composite traffic factor.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation